2015
DOI: 10.1017/s0007114515003657
|View full text |Cite
|
Sign up to set email alerts
|

A Western dietary pattern is associated with overweight and obesity in a national sample of Lebanese adolescents (13–19 years): a cross-sectional study

Abstract: Adolescent obesity is associated with both immediate and longer-term health implications. This study aims to identify dietary patterns among a nationally representative sample of Lebanese adolescents aged between 13 and 19 years (n 446) and to assess the association of these patterns with overweight and obesity. Through face-to-face interviews, socio-demographic, lifestyle and anthropometric variables were collected. Dietary intake was assessed using a sixty-one-item FFQ. Dietary patterns were derived by facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
139
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 62 publications
18
139
0
15
Order By: Relevance
“…Similarly, the traditional Lebanese pattern, which builds on higher intakes of breads and cereals, dairy products, fruits and vegetables and traditional Lebanese mixed dishes, is similar to the Traditional pattern reported in previous studies conducted amongst adolescents and adults in the country [38][39][40]. In agreement with our findings, Lioret et al and Manios et al have also identified two dietary patterns amongst French and Greek preschoolers, respectively, with the identified patterns being similar to those derived in the present study, even though the specific foods belonging to each pattern may vary in their respective level of contribution [18,19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, the traditional Lebanese pattern, which builds on higher intakes of breads and cereals, dairy products, fruits and vegetables and traditional Lebanese mixed dishes, is similar to the Traditional pattern reported in previous studies conducted amongst adolescents and adults in the country [38][39][40]. In agreement with our findings, Lioret et al and Manios et al have also identified two dietary patterns amongst French and Greek preschoolers, respectively, with the identified patterns being similar to those derived in the present study, even though the specific foods belonging to each pattern may vary in their respective level of contribution [18,19].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the use of factor analysis requires several arbitrary assumptions relevant to the selection of food groups, the number of retained factors and their labeling [61]. The food groupings that were adopted in this study were comparable with those performed in previous investigations amongst Lebanese adults [39,40,62] and adolescents [38]. Lastly, in this study, there was no information about a few factors that may also affect overweight/ obesity among children such as maternal pre-pregnancy BMI, gestational weight gain and breastfeeding as well as the level of physical activity of the child [63,64].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, we used a validated FFQ to examine food intake. The percentage of variance explained by the dietary patterns was within the range of what has been previously reported in other studies that studied dietary patterns of adolescents [30,43,54,55].…”
Section: Discussionsupporting
confidence: 86%
“…The justification of this idea is that it has been consistently demonstrated that, compared to obesity in early childhood, obesity in adolescence is a strong predictor of obesity in adulthood, the probability that obesity in adolescence will persist in adulthood having risen by 80%. 24 Given our findings, the discrepancy regarding eating habits declared by children and what their parents believe shows, apart from a technically low concordance, a tendency in the discrepancy which conceptually represents an increased risk of obesity. In summary, considerable ignorance was found among parents with regard to whether their children eat healthily (fruit and vegetables), eat breakfast or not, follow a diet or not, and whether they eat alone or not.…”
Section: Discussionmentioning
confidence: 55%